Impovement of some functional properties of cookies with added natural components of pumpkin and chia - Ditrikh, Iryna; Moiseieva, Valeriia (My University, 2017)
A new type of cookie "Pumpkin" has the high biological value due to the introduction of raw materials of plant origin into its composition – hydrolysed pumpkin puree and pumpkin oil, chia seeds. The optimal concentration of pumpkin puree, pumpkin oil and chia seeds for harmonic taste and smell are established. Sensory, physical and chemical parameters are investigated.
Keywords: печиво гарбузове; насіння чіа; олія гарбуза; пюре гарбузове; рumpkin oil; рumpkin puree; кафедра технології ресторанної і аюрведичної продукції